2016
DOI: 10.1126/scitranslmed.aaf9387
|View full text |Cite
|
Sign up to set email alerts
|

A replication-defective human cytomegalovirus vaccine for prevention of congenital infection

Abstract: Congenital human cytomegalovirus (HCMV) infection occurs in ~0.64% of infants born each year in the United States and is the leading nongenetic cause of childhood neurodevelopmental disabilities. No licensed HCMV vaccine is currently available. Natural immunity to HCMV in women before pregnancy is associated with a reduced risk of fetal infection, suggesting that a vaccine is feasible if it can reproduce immune responses elicited by natural infection. On the basis of this premise, we developed a whole-virus va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 51 publications
2
94
0
Order By: Relevance
“…This vaccine, designed by Merck Vaccines, has a restored, wild-type PC sequence in which the frameshift mutation in the first exon of UL131-a mutation that underlies the epithelial tropism deficiency in AD169 resulting from abrogation of proper assembly of the PC-was repaired in Escherichia coli by recombineering of an infectious bacterial artificial chromosome (BAC) clone of the AD169 genome, followed by recovery of repaired virus harvested after transfection of BAC DNA onto human retinal pigmented epithelial (ARPE-19) cells. V160 was further modified such that viral proteins IE1/IE2 and UL51 were expressed as fusion proteins with FKBP12, a rapamycin-binding protein (102)(103)(104). Since UL51 and IE1/2 are essential for replication competence (105,106), V160 is able to propagate in ARPE-19 cells only in the presence of a synthetic stabilizing ligand, Shield-1.…”
Section: Live Attenuated and "Disc" Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…This vaccine, designed by Merck Vaccines, has a restored, wild-type PC sequence in which the frameshift mutation in the first exon of UL131-a mutation that underlies the epithelial tropism deficiency in AD169 resulting from abrogation of proper assembly of the PC-was repaired in Escherichia coli by recombineering of an infectious bacterial artificial chromosome (BAC) clone of the AD169 genome, followed by recovery of repaired virus harvested after transfection of BAC DNA onto human retinal pigmented epithelial (ARPE-19) cells. V160 was further modified such that viral proteins IE1/IE2 and UL51 were expressed as fusion proteins with FKBP12, a rapamycin-binding protein (102)(103)(104). Since UL51 and IE1/2 are essential for replication competence (105,106), V160 is able to propagate in ARPE-19 cells only in the presence of a synthetic stabilizing ligand, Shield-1.…”
Section: Live Attenuated and "Disc" Vaccinesmentioning
confidence: 99%
“…Since UL51 and IE1/2 are essential for replication competence (105,106), V160 is able to propagate in ARPE-19 cells only in the presence of a synthetic stabilizing ligand, Shield-1. Since Shield-1 is not found in nature, the fusion protein is rapidly degraded and viral replication is inhibited in any immunized subject (103,104), providing an excellent safety profile for the vaccine. V160 has recently completed phase I testing.…”
Section: Live Attenuated and "Disc" Vaccinesmentioning
confidence: 99%
“…Using this virus vaccine, it was shown in rabbits that the PC is the primary target for potent neutralizing antibodies [93,94], which are able to display antiviral activity against a panel of genetically distinct HCMV clinical isolates [95]. The same vaccine, when made conditionally replicationdefective, was shown to elicit a durable neutralizing antibody response and a T cell (both CD4 + and CD8 + ) response to multiple viral antigens in non-human primates (rhesus macaques) [96].…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…The PC is considered an important neutralizing antibody target for virus infection of epithelial, endothelial and trophoblast cells (26, 29). Therefore this complex has emerged as a potentially important component of a CMV vaccine target against congenital CMV (26, 84, 85). The guinea pig is the only small animal model for congenital CMV and a previous report from our laboratory demonstrated that GPCMV forms a homolog PC (gH/gL/GP129/GP131/GP133) which was necessary for epithelial cell tropism and dissemination in vivo with dramatically increased congenital infection rate.…”
Section: Discussionmentioning
confidence: 99%